2017
DOI: 10.1098/rsta.2016.0001
|View full text |Cite
|
Sign up to set email alerts
|

On the effective stress law for rock-on-rock frictional sliding, and fault slip triggered by means of fluid injection

Abstract: Fluid injection into rocks is increasingly used for energy extraction and for fluid wastes disposal, and can trigger/induce small- to medium-scale seismicity. Fluctuations in pore fluid pressure may also be associated with natural seismicity. The energy release in anthropogenically induced seismicity is sensitive to amount and pressure of fluid injected, through the way that seismic moment release is related to slipped area, and is strongly affected by the hydraulic conductance of the faulted rock mass. Bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 47 publications
10
62
0
1
Order By: Relevance
“…A mean pore pressure of 10.0 MPa and an axial loading rate of 0.05 mm/min was used in all experiments. The previous results of Rutter and Hackston (2017) showed that under these conditions, the effective pressure law applies to Pennant sandstone without dilatancy hardening effects becoming apparent. Rutter and Mecklenburgh (2017) found that the same was true of Bowland shale when argon gas was used as pore fluid.…”
Section: 1002/2017jb014858mentioning
confidence: 99%
See 1 more Smart Citation
“…A mean pore pressure of 10.0 MPa and an axial loading rate of 0.05 mm/min was used in all experiments. The previous results of Rutter and Hackston (2017) showed that under these conditions, the effective pressure law applies to Pennant sandstone without dilatancy hardening effects becoming apparent. Rutter and Mecklenburgh (2017) found that the same was true of Bowland shale when argon gas was used as pore fluid.…”
Section: 1002/2017jb014858mentioning
confidence: 99%
“…A large, homogeneous block was obtained from a monumental mason. Samples from the same block were used in rock mechanics studies by Hackston and Rutter (2016) and Rutter and Hackston (2017). Pennant sandstone displays a weak grain shape orientation parallel to bedding (Figure 1), but the bedding orientation is not well defined by microstructural layering or inhomogeneities.…”
Section: Test Materials and Experiments Performedmentioning
confidence: 99%
“…This was expected to ensure that the breakdown pressure was independent of pressurization rate, following Zoback et al () who suggest that the dependence on rate that they observe in constant pressurization rate experiments was caused by diffusion of the injection fluid into the samples at lower pressurization rates. It might be expected that this effect would be significantly smaller for the materials tested here, which have permeabilities on the order of 10 −19 m 2 (Rutter & Hackston, ), as opposed to the ≃10 −16 m 2 of the materials tested by Zoback et al…”
Section: Methodsmentioning
confidence: 76%
“…Mechanical properties of shales are of interest due to the worldwide exploitation of gas shale resources, as source or cap rocks in oil and gas exploration, and as a potential repository for radioactive waste. Hydraulic fracturing has become increasingly commonplace as a method of increasing hydrocarbon recovery from low‐permeability reservoir rocks such as shale and tight sandstones, leading to increased interest in fracture growth properties in these materials (Rutter & Hackston, ). This increased interest has led to a number of recent studies investigating fracture mechanics properties in shale materials both through experimental measurements (Chandler et al, , ; Forbes Inskip et al, ; Lee et al, ; Luo et al, ) and modeling studies (Dutler et al, ; Gao et al, ; Zia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of this unstable behaviour is that when the inhomogeneity of the fault is enhanced (in this case by roughness), weak patches are formed due to normal stress fluctuations which act as stress concentrators and initiators of instability. As reported in the experimental study proposed by Rutter & Hackston [84], a stable-sliding fault can also become seismic under the effect of a fluid injection. Here, too, we note that the effect of inhomogeneity is crucial, as rupture is triggered when the rate of injection is high, preventing pressure diffusion to a larger zone and creating a localized region of low effective normal stress.…”
Section: Challenging Observations (A) Dissipation: Is It Only Friction?mentioning
confidence: 79%